Morphological and physiological specialization for digging in amphisbaenians, an ancient lineage of fossorial vertebrates - Navas, C. A.; Antoniazzi, M. M.; Carvalho, J. E.; Chaui-Berlink, J. G.; James, R. S.; Jared, C.; Kohlsdorf, T.; Dal Pai-Silva, M.; Wilson, R. S. (Company of Biologists Ltd, 2004)
Amphisbaenians are legless reptiles that differ significantly from other vertebrate lineages. Most species dig underground galleries of similar diameter to that of the animal. We studied the muscle physiology and morphological attributes of digging effort in the Brazilian amphisbaenid Leposternon microcephalum (Squamata; Amphisbaenia), which burrows by compressing soil against the upper wall of the tunnel by means of upward strokes of the head. The individuals tested (<72 g) exerted forces on the soil of up to 24 N. These forces were possible because the fibres of the longissimus dorsi, the main muscle associated with burrowing, are highly pennated, thus increasing effective muscle cross-sectional area. The muscle is characterized by a metabolic transition along its length: proximal, medial and distal fibres are fast contracting and moderately oxidative, but fibres closer to the head are richer in citrate synthase and more aerobic in nature. Distal fibres, then, might be active mainly at the final step of the compression stroke, which requires more power. For animals greater than a given diameter, the work required to compress soil increases exponentially with body diameter. Leposternon microcephalum, and probably some other highly specialized amphisbaenids, are most likely constrained to small diameters and can increase muscle mass and effective muscle cross-sectional area by increasing body length, not body diameter.
Keywords: Amphisbaenia; reptile; muscle; digging; Leposternon microcephalum